Review of the Article on the Provisions of Tawassul by the Prophet, may Allah Bless him and Grant him Peace - an Original Study - - Mustafa , Hussein (Islamic Sciences Journal, 2023)
ABSTRACT Al- Wasilah is a legitimate sacrifice by which the worshipper attains a gool and fulfills a desire. Al- tawassul is to draw closer to Allah with that nearness, and tawassul is the request of the caller based on that kinship. There is no one in the law of Islam that is required and called except for Allah, and this is what has been legislated for this nation in the book of its Lord and on the tongue of its Prophet. Since Al-tawassul is a purely doctrinal issue that revolves between disbelief and faith, so the worshipper should perform it based on clear evidence that cannot be interpreted, keeping away from ambiguous ones, weak evidence, and correct conjecture, meaning that Al-tawassul is either begging with Allah’s attributes and names, or with what He has a valid belief, or because of his good deeds, or because of the supplication of others. As for what was not provided with definitive evidence from the wise legislator of its permissibility, then it is better for the worshipper to leave it and stay away from it because of the suspicion that the perpetrator might expect in what does not please Allah, and whoever avoids suspicions has cleared himself of his religion and his honor.